Selection and Analysis Performance of the Rechargeable Battery for Electric Go-kart Development - Amir Hamzah, Muhammad Haikal (Progress in Engineering Application and Technology, 2022)
Most go-karts built for marketing purposes and racing on the circuit use Gasoline (petrol). The use of gas does more harm than good, especially to the environment. The objective of this project is to select the best rechargeable battery that can be used for an electric go-kart. This selection for the rechargeable battery is based on the criteria and description by research on the available source such as the Internet and depends on the entire go-kart electric system, especially for the electric motor. The primary things for the rechargeable batteries such as lead-acid, nickel-cadmium (NiCd), nickel-metal hydride (NiMH), lithium-ion (Li-ion), lithium-ion polymer (LiPo), and all rechargeable alkaline batteries are being researched thoroughly to understand the combinations of chemicals reaction are used in this battery. In order to obtain the best battery, it has to be parallel with the scope of the project and suited to the criteria needed. Several types of rechargeable batteries are listed, and final decisions are chosen based on the criteria needed. The final phase of this project is to assemble all the components and parts of the electric go-kart. The purpose of this project carried out is to ensure the battery is suited to the requirement of the entire electric system and its use can last longer.